Cement paste system and preparation method thereof
By using a combination of high-temperature anti-decay agent, water loss reducing agent, retarder and defoaming agent in the high-density cement slurry system, a high-density cement slurry without weighting agents is constructed, which solves the construction difficulty and performance problems caused by weighting agents in the prior art, and achieves high-density, good fluidity and high compressive strength cement slurry.
Patent Information
- Application Number
- CN202411664004.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-20
- Publication Date
- 2025-02-25
AI Technical Summary
The existing high-density cement slurry system requires adding weighting agents to achieve the design density, resulting in high solid phase content, high construction difficulty, and easy settlement in high temperature environments, affecting performance.
By using a combination of high-temperature anti-decay agent, water reduction agent, retarder and defoaming agent, a high-density cement slurry system without advancing agents is constructed to ensure the optimization of cement slurry density, fluidity and compressive strength.
The cement slurry density reaches 2.4g/cm3, good fluidity, low API water loss, adjustable thickening time, no free liquid production, high compressive strength, and long-term compressive strength does not decline. It is suitable for cementing technology in special wells such as high-temperature and high-pressure wells.
Smart Images

Figure CN119504191A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of oilfield chemistry, and relates to a cement slurry system and a preparation method thereof, in particular to a high-density cement slurry system without a weighting agent and a preparation method thereof. Background Art
[0002] With the consumption of shallow oil and natural gas resources and the improvement of exploration and development technology, oil and gas field exploitation is facing more complex wells and ultra-deep well conditions, and the difficulty of oil and gas development is increasing. Deep wells and ultra-deep wells often encounter high pore pressure, unstable well walls, and abnormally high-pressure gas layers during drilling. In cementing operations, facing these high-pressure gas layers, high static liquid column pressure must be used for control. Researchers often use high-performance and high-density cement slurry systems for cementing operations, which can balance the formation pressure, stabilize the formation, and effectively prevent gas channeling and blowouts. High-density cement slurry generally refers to a density greater than 1.9g / cm 3 of cement slurry.
[0003] In order to increase the density of cement slurry, it is often necessary to add weighting agents to prepare high-density cement slurry. Weighting agents are materials that increase the density of cement slurry while improving the cement slurry's mixing ability and slurry fluidity. They include barite, iron ore powder, manganese ore powder, pure iron powder, etc. Generally, the density of cement slurry can be increased to 2.3-2.6g / cm 3 ;
[0004] The Chinese invention patent application number 202111094447.6 discloses a low-friction high-density cement slurry and a preparation method thereof. The components and weights of the low-friction high-density cement slurry are as follows: 100 parts of G-grade oil well cement, 30 240 parts of weighting material, 10 30 parts of reinforcing material, 0.3 3 parts of early strength stabilizer, 0.5 2 parts of polycarboxylic acid dispersant, 0.5 4 parts of fluid loss reducer, and 0.2 2 parts of retarder; the density range of the cement slurry is 2.1 3.0 g / cm 3 The weighting material is a micro-nano spherical particle weighting agent, which not only plays a role in weighting, but also plays a "ball" lubrication role, effectively reducing friction.
[0005] The Chinese invention patent with application number 202111581207.9 discloses a nano high-density anti-channeling cement slurry and a preparation method, by adding nano zinc oxide as a weighting agent; compared with the ground iron ore powder weighting agent in the prior art (average particle size of 100μm 300μm or more), the particle size is finer and the density is higher; the nano magnesium oxide dispersion is filled in the gaps between cement particles, which has the effect of reducing API water loss and reducing the permeability of cement stone; at the same time, the nano magnesium oxide gradually hydrates to form nano magnesium hydroxide after the cement slurry solidifies, and the volume expansion of the nano particles can significantly control the shrinkage performance of the cement stone.
[0006] The Chinese invention patent with application number 202210052442.5 discloses a high-density anti-channeling tough cement slurry system for shale gas cementing, and its preparation method and application, including G-grade cement, water, composite weighting agent, nano anti-channeling agent, toughening agent, fluid loss reducer, retarder, dispersant and defoamer. The invention uses a composite weighting agent with a mass ratio of manganese ore powder to iron ore powder of 2:1. The elastic modulus of cement stone using the composite weighting agent is lower than that of cement stone formed by conventional weighting agents, and has little effect on mechanical properties such as impact strength.
[0007] The prior art represented by the above patents uses different types of weighting agents in the construction of high-density cement slurry systems, which has achieved breakthroughs in cement slurry performance. However, the existing system still has some disadvantages, which are mainly reflected in the following points: (1) The solid content is high, making it difficult to mix the cement on the ground during construction; (2) High-density cement slurry is mostly used in high-temperature environments, and a large amount of silica powder needs to be added as an anti-thermal decay agent, which further increases the solid content and affects the mixing ability; (3) The viscosity is high at room temperature, and the cement and weighting agent are easy to settle at high temperatures at the bottom of the well; (4) The weighting agent is an inert material with a high content, and the cement content is relatively low, so the strength develops slowly, and the cement on the top may be super-retarded. In summary, the most critical point is that since the existing high-density cement slurry systems all require the addition of weighting agents to be constructed, it is impossible to ensure a balance between the design density and the engineering performance of the cement slurry. Summary of the invention
[0008] In view of the defects of the prior art, the present invention provides a cement slurry system and a preparation method thereof.
[0009] Specifically, the cement slurry system provided by the present invention includes: cement, high-temperature anti-fading agent, fluid loss reducer, retarder, and defoamer.
[0010] The cement slurry system comprises, by weight, 100 parts of cement, 30-70 parts of high-temperature anti-fading agent, 1-8 parts of fluid loss reducer, 0.5-4 parts of retarder, and 0.1-1 parts of defoamer.
[0011] The cement slurry system comprises, by weight, 100 parts of cement, 35-50 parts of high-temperature anti-fading agent, 2-7 parts of fluid loss reducer, 1-3 parts of retarder, and 0.5-1 parts of defoamer.
[0012] The cement slurry system mentioned above is Grade G oil well cement that meets API specifications.
[0013] In the above cement slurry system, the high temperature anti-fading agent is composed of spherical silicon dioxide with a crystalline structure and micro-silicon with an amorphous structure in a mass ratio of 6-8:1.
[0014] In the cement slurry system, the high-temperature anti-fading agent is composed of spherical silicon dioxide with a crystalline structure and micro-silicon with an amorphous structure in a mass ratio of 7:1.
[0015] In the cement slurry system, the sphericity of the spherical silicon dioxide is greater than 96%, and the particle size is 4-10 μM; the average particle size of the microsilicon is 0.1-1 μM.
[0016] In the above-mentioned cement slurry system, the fluid loss reducer is a graft copolymer of fulvic acid salt.
[0017] In the cement slurry system, the fluid loss reducer is a copolymer of fulvic acid salt grafted with 2-acrylamide-2-methylpropanesulfonic acid, N-methylpyrrolidone, methacrylic anhydride and dimethylaminoethyl acrylate.
[0018] In the above-mentioned cement slurry system, the humate is sodium humate or potassium humate.
[0019] In the above-mentioned cement slurry system, the weight ratio of humate to 2-acrylamide-2-methylpropanesulfonic acid, N-methylpyrrolidone, methacrylic anhydride and dimethylaminoethyl acrylate in the fluid loss reducer is (4-7): (55-77): (6-13): (0.5-3): (2-6).
[0020] In the cement slurry system, the retarder is obtained by compounding lignin sulfonate and AMPS copolymer.
[0021] In the above-mentioned cement slurry system, the lignin sulfonate is sodium lignin sulfonate or calcium lignin sulfonate.
[0022] In the above-mentioned cement slurry system, the weight ratio of the lignin sulfonate to the AMPS copolymer is (0.5:4.5)-(1:4).
[0023] In the above-mentioned cement slurry system, the defoaming agent is an ester defoaming agent, an organosilicon defoaming agent or a silicone ether oil defoaming agent.
[0024] The preparation method of the cement slurry system provided by the present invention comprises:
[0025] (1) weighing cement and high-temperature anti-fading agent according to a proportion, mixing and stirring to obtain a solid mixture;
[0026] (2) weighing water, fluid loss reducer, retarder, and defoamer according to the proportion, mixing, and obtaining slurry water;
[0027] (3) adding the solid mixture into the slurry preparation water within 15 seconds at a first stirring speed, and mixing at a second stirring speed to obtain a cement slurry system.
[0028] In the above-mentioned method for preparing the cement slurry system, the first stirring speed is 4000±200 rpm; the second stirring speed is 12000±500 rpm.
[0029] In the preparation method of the cement slurry system, the fluid loss reducer is prepared by the following method:
[0030] (1) stirring and dissolving 2-acrylamide-2-methylpropanesulfonic acid, N-methylpyrrolidone, methacrylic anhydride, dimethylaminoethyl acrylate, and fulvic acid salt in water according to a proportion to obtain a mixed solution;
[0031] (2) adding alkali to adjust the pH of the mixed solution to 3-5, heating to 58-62° C., introducing nitrogen for 10-30 minutes, initiating the reaction with an initiator, and reacting for 4-6 hours to obtain a fluid loss reducer.
[0032] In the preparation method of the cement slurry system, the alkali is sodium hydroxide; and the initiator is sodium sulfate, potassium persulfate, ammonium persulfate or azobisisobutylamidine hydrochloride.
[0033] The technical solution of the present invention has the following beneficial effects:
[0034] (1) The high-density cement slurry system of the present invention can achieve a maximum cement slurry density of 2.4 g / cm without adding a weighting agent. 3 It has the characteristics of good cement slurry fluidity, low API water loss, adjustable thickening time, no free liquid generation, high compressive strength, and no long-term compressive strength decline. The system formula is simple and convenient for offshore construction.
[0035] (2) The cement slurry system provided by the present invention can meet the cementing technical requirements of special wells such as high-temperature and high-pressure wells, deep wells, ultra-deep wells, and salt-gypsum layer wells. BRIEF DESCRIPTION OF THE DRAWINGS
[0036] Various other advantages and benefits will become apparent to those of ordinary skill in the art by reading the following detailed description of the preferred embodiment.The drawings are only for the purpose of illustrating the preferred embodiments and are not to be construed as limiting the invention.
[0037] Figure 1 2.3 g / cm2 of Example 1 of the present invention 3 Thickening time curve of cement slurry system at 120℃;
[0038] Figure 2 2.3 g / cm2 of Example 2 of the present invention 3 Thickening time curve of cement slurry system at 150℃;
[0039] Figure 3 2.3 g / cm2 of Example 3 of the present invention 3Thickening time curve of cement slurry system at 180℃;
[0040] Figure 4 2.4 g / cm2 of Example 4 of the present invention 3 Thickening time curve of cement slurry system at 180℃;
[0041] Figure 5 2.3 g / cm2 of Example 5 of the present invention 3 Thickening time curve of cement slurry system at 210℃;
[0042] Figure 6 2.4 g / cm2 of Example 6 of the present invention 3 Thickening time curve of cement slurry system at 210℃. DETAILED DESCRIPTION
[0043] In order to fully understand the purpose, features and effects of the present invention, the present invention is described in detail through the following specific embodiments. Except for the following contents, the process method of the present invention adopts conventional methods or devices in the art. Unless otherwise specified, the following terms have the meanings commonly understood by those skilled in the art.
[0044] In a first aspect, the cement slurry system provided by the present invention does not contain any weighting agent and includes: cement, a high-temperature anti-fading agent, a fluid loss reducer, a retarder, and a defoaming agent.
[0045] Cement slurry is a complex component. On the basis of base cement, various additives are often added to meet the downhole temperature and pressure conditions to ensure construction safety during cementing in oil and gas wells and the long-term integrity of cement sheath isolation.
[0046] The components of the cement slurry system of the present invention are described in detail below:
[0047] cement
[0048] In some preferred embodiments, the cement used in the present invention is Grade G oil well cement that meets API specifications.
[0049] Grade G cement is the basic cement in the API specification and national standard. It is suitable for a wider range of well depths and temperatures. The thickening time is required to be 90-120 minutes. It also has requirements for free liquid to prevent the cement slurry from affecting the cementing quality due to excessive free liquid.
[0050] High temperature anti-fading agent
[0051] Under high temperature (generally over 110°C), due to the transformation of the crystal form of the hydration product, a crystal phase with high permeability and low strength is formed, and the strength of the cement paste will decline significantly. It is often necessary to add high-temperature anti-decay agents, which participate in the cement hydration process and change the crystal form of the cement hydration product to prevent strength decline.
[0052] In some preferred embodiments, the high temperature anti-fading agent used in the present invention is composed of spherical silicon dioxide with a crystalline structure and micro-silicon with an amorphous structure in a mass ratio of (6-8):1 (more preferably 7:1).
[0053] Further preferably, the sphericity of the spherical silica is greater than 96%, and the particle size is 4-10 μM; the average particle size of the micro-silicon is 0.1-1 μM.
[0054] The high-temperature anti-fading agent used in the present invention is a composite of spherical silicon dioxide with a crystal structure and micro-silicon with an amorphous structure. The addition of a silicon source can adjust the calcium-silicon ratio in the cement system, so that the cement paste maintains a high strength and a low permeability. On the one hand, the spherical silicon dioxide can utilize the ball effect to enhance the fluidity of the cement slurry during mixing. On the other hand, the two different crystal forms of silicon dioxide have different dissolution reaction rates, which can provide sufficient silicon sources in both short-term and long-term high-temperature curing, participate in the cement liquid phase hydration reaction, and maintain long-term stability.
[0055] In some preferred embodiments, based on 100 parts by weight of cement, the proportion of the high temperature anti-fading agent in the cement slurry system of the present invention is 30-70 parts.
[0056] If the content of high temperature anti-decay agent is too little, it cannot effectively react with cement hydration products, and will still produce high permeability and low strength hydration products, which cannot prevent the strength decline of cement paste; if the content of high temperature anti-decay agent is too much, it may take a long time to ash, which will affect the mixing performance of cement slurry and the fluidity of cement slurry. Moreover, too much anti-decay agent will dissolve silicon under long-term curing, which will still have an adverse effect on the long-term strength of cement paste.
[0057] Further preferably, based on 100 parts by weight of cement, the proportion of the high temperature anti-fading agent in the cement slurry system of the present invention is 35-50 parts.
[0058] Fluid Loss Additive
[0059] During cementing construction, cement slurry will filter to both sides of the formation under pressure. If the cement slurry loses too much water, it will affect the cement slurry density, thickening time, fluidity and other properties. In addition, the filtrate entering the reservoir will cause damage to the formation. In order to reduce water loss, a fluid loss reducer is often added.
[0060] In some preferred embodiments, the fluid loss additive used in the present invention is a graft copolymer of fulvic acid salt.
[0061] Further preferably, the fluid loss additive is a copolymer of fulvic acid salt grafted with 2-acrylamide-2-methylpropanesulfonic acid, N-methylpyrrolidone, methacrylic anhydride and dimethylaminoethyl acrylate.
[0062] The fluid loss reducer used in the present invention is a low-viscosity fluid loss reducer, which is a graft copolymer of fulvic acid salt. Fulvic acid contains multiple aromatic rings and heterocyclic rings. After being adsorbed on the surface of cement particles, it forms a huge three-dimensional structure, so that the cement particles are dispersed. When high-density cement slurry is configured, the slurry has good fluidity. 2-Acrylamide-2-methylpropanesulfonic acid has a sulfonic acid group with an adsorption group, which can be adsorbed on the surface of cement particles. At the same time, it has an amide group with hydration ability, which can bind water molecules in the slurry and reduce water loss. N-methylpyrrolidone is a cyclic rigid monomer, which can provide certain heat resistance for the fluid loss reducer. Methacrylic anhydride contains two carboxylic acid groups after hydrolysis, has adsorption capacity, and enhances the ability to adsorb on the surface of cement particles at high temperatures. Dimethylaminoethyl acrylate has an ester group, which is hydrolyzed into a carboxyl group at high temperatures and can be adsorbed on the surface of cement particles. At the same time, it contains a hydrophobic alkyl chain, which will associate at high temperatures and reduce the sedimentation of cement slurry at high temperatures.
[0063] In some preferred embodiments, the weight ratio of fulvic acid salt to 2-acrylamide-2-methylpropanesulfonic acid, N-methylpyrrolidone, methacrylic anhydride and dimethylaminoethyl acrylate in the fluid loss reducer is (4-7): (55-77): (6-13): (0.5-3): (2-6).
[0064] In some preferred embodiments, the fulvic acid salt is sodium fulvic acid or potassium fulvic acid.
[0065] In some preferred embodiments, the fluid loss additive used in the present invention is prepared by the following method:
[0066] (1) stirring and dissolving 2-acrylamide-2-methylpropanesulfonic acid, N-methylpyrrolidone, methacrylic anhydride, dimethylaminoethyl acrylate, and fulvic acid salt in water according to a proportion to obtain a mixed solution;
[0067] (2) adding alkali to adjust the pH of the mixed solution to 3-5, heating to 58-62° C., introducing nitrogen for 10-30 minutes, initiating the reaction with an initiator, and reacting for 4-6 hours to obtain a fluid loss reducer.
[0068] Wherein, the base is sodium hydroxide, and the initiator is sodium sulfate, potassium persulfate, ammonium persulfate or azobisisobutyramidine hydrochloride.
[0069] In some preferred embodiments, based on 100 parts by weight of cement, the proportion of the fluid loss reducer in the cement slurry system of the present invention is 1-8 parts.
[0070] If the amount of fluid loss agent added is too little, the water control ability of the cement slurry will be poor; if the amount of fluid loss agent added is too much, the fluidity of the cement slurry will deteriorate.
[0071] Further preferably, based on 100 parts by weight of cement, the proportion of the fluid loss reducer in the cement slurry system of the present invention is 2-7 parts.
[0072] Retarder
[0073] The setting time of cement paste is generally 90-120 minutes. In order to ensure the safety of oil and gas well cementing operations, retarders are often added to extend the setting time of cement slurry.
[0074] In some preferred embodiments, the retarder is obtained by compounding lignin sulfonate and AMPS copolymer.
[0075] The dispersed retarder used in the present invention is a mixture of lignin sulfonate and AMPS copolymer. The lignin sulfonate has a highly branched molecular chain and can further reduce the flow resistance of the cement slurry when used in a high-density cement slurry system. The compounding of lignin sulfonate and AMPS copolymer can achieve a multifunctional agent, so that the retarder has both the properties of retarding and dispersing.
[0076] In some preferred embodiments, the weight ratio of the lignin sulfonate to the AMPS copolymer is (0.5:4.5)-(1:4).
[0077] Among them, AMPS copolymer is a copolymer of 2-acrylamide-2-methylpropanesulfonic acid and methacrylic acid (MAA), and its molecular weight is between 200,000 and 300,000.
[0078] Wherein, the lignin sulfonate is sodium lignin sulfonate or calcium lignin sulfonate.
[0079] In some preferred embodiments, the retarder can be purchased from C-R41L produced by Blue Ocean Boda Technology Co., Ltd.
[0080] In some preferred embodiments, based on 100 parts by weight of cement, the proportion of the retarder in the cement slurry system of the present invention is 0.5-4 parts.
[0081] If the amount of retarder added is too little, there will be risks in the cementing operation, and the cement slurry may solidify prematurely underground; if the amount of retarder added is too much, it may be over-retarded and the thickening time will be too long, causing inconvenience to subsequent drilling or development.
[0082] Further preferably, based on 100 parts by weight of cement, the proportion of the retarder in the cement slurry system of the present invention is 1-3 parts.
[0083] Defoaming agent
[0084] Bubbles will be generated during the high-speed stirring process of mixed water and cement slurry. The presence of bubbles will affect the cement slurry's mixing ability, density and other properties. Therefore, defoaming agents need to be added to reduce bubbles.
[0085] In some preferred embodiments, the defoaming agent is an ester defoaming agent, a silicone defoaming agent or a silicone ether oil defoaming agent.
[0086] Among them, the ester defoaming agent is, for example, dipalmitoyl ethylenediamine and sorbitan monolaurate; the silicone defoaming agent is, for example, polydimethylsiloxane; and the silicone ether oil defoaming agent is, for example, polyoxypropylene glycerin and polyoxyethylene polyoxypropylene glycerin.
[0087] In some preferred embodiments, the defoaming agent in the cement slurry system of the present invention is contained in an amount of 0.1-2 parts by weight based on 100 parts by weight of cement.
[0088] When the defoaming agent content is too little, a large number of bubbles will be generated, which may easily lead to cementing accidents; when the defoaming agent content is too much, a large amount of oily substances will be mixed into the cement slurry, affecting the bonding of cement stone.
[0089] Further preferably, based on 100 parts by weight of cement, the ratio of the defoamer in the cement slurry system of the present invention is 0.5-1 part.
[0090] In a second aspect, the present invention further provides a method for preparing a cement slurry system, comprising:
[0091] (1) weighing cement and high-temperature anti-fading agent according to a proportion, mixing and stirring to obtain a solid mixture;
[0092] (2) weighing water, fluid loss reducer, retarder, and defoamer according to the proportion, mixing, and obtaining slurry water;
[0093] (3) adding the solid mixture into the slurry preparation water within 15 seconds at a first stirring speed, and mixing at a second stirring speed to obtain a cement slurry system.
[0094] In some preferred embodiments, the first stirring speed is 4000±200 rpm; the second stirring speed is 12000±500 rpm.
[0095] The compositions and proportions of cement, high temperature anti-fading agent, fluid loss reducer, retarder and defoaming agent used in the cement slurry preparation method of the present invention are the same as those in the cement slurry system mentioned in the first aspect of the present invention, and the present invention will not repeat them here.
[0096] Example
[0097] The present invention is further described below by way of examples, but the present invention is not limited to the scope of the examples. The experimental methods in the following examples without specifying specific conditions are carried out according to conventional methods and conditions. The raw materials used in the following examples are all conventionally purchased.
[0098] The retarder was purchased from C-R41L produced by Blue Ocean Boda Technology Co., Ltd.
[0099] The defoamer was purchased from C-DF60L produced by Blue Ocean Boda Technology Co., Ltd.
[0100] Example 1
[0101] Cement slurry test temperature: 120℃ Cement slurry density: 2.3g / cm 3
[0102] (1) 600 g of G-grade cement and 210 g of high-temperature anti-fading agent are mixed to obtain a solid mixture.
[0103] (2) Weigh 112 g of water, 24 g of fluid loss reducer, 6 g of retarder C-R41L, and 3 g of C-DF60L, and mix to obtain slurry water;
[0104] The high temperature anti-fading agent is a compound of spherical silicon dioxide with a crystal structure and micro silicon with an amorphous structure in a mass ratio of 7:1. The sphericity of the spherical silicon dioxide is greater than 96%, and the particle size is between 4-10μM. The micro silicon is a gray powder with an average particle size of 0.1-1μM.
[0105] The specific preparation method of the fluid loss reducer is as follows: A. weigh 56.7g of 2-acrylamide-2-methylpropane sulfonic acid, 6.3g of N-methylpyrrolidone, 0.82g of methacrylic anhydride, 2.3g of dimethylaminoethyl acrylate, and 4.5g of sodium humate for later use; B. stir and dissolve 2-acrylamide-2-methylpropane sulfonic acid, N-methylpyrrolidone, methacrylic anhydride, dimethylaminoethyl acrylate, and sodium humate in water to obtain a mixed solution; C. adjust the pH of the mixed solution to 4.2 with sodium hydroxide; heat to 61.7° C., introduce nitrogen for 15 minutes, add an initiator sodium persulfate to initiate, and react for 4 hours to obtain a fluid loss reducer;
[0106] (3) adding the solid mixture into the slurry preparation water within 15 seconds at a stirring speed of 4000±200 rpm, and stirring for 35 seconds at a stirring speed of 12000±500 rpm to obtain a cement slurry system.
[0107] Example 2
[0108] Cement slurry test temperature: 150℃ Cement slurry density: 2.3g / cm 3
[0109] (1) 600 g of G-grade cement and 210 g of high-temperature anti-fading agent are mixed to obtain a solid mixture.
[0110] (2) Weigh 109 g of water, 28 g of fluid loss reducer, 9 g of retarder C-R41L, and 3 g of C-DF60L, and mix to obtain slurry water;
[0111] The high temperature anti-fading agent is a compound of spherical silicon dioxide with a crystal structure and micro silicon with an amorphous structure in a mass ratio of 7:1. The sphericity of the spherical silicon dioxide is greater than 96%, and the particle size is between 4-10μM. The micro silicon is a gray powder with an average particle size of 0.1-1μM.
[0112] The specific preparation method of the fluid loss reducer is as follows: a. weigh 51.4.g of 2-acrylamide-2-methylpropane sulfonic acid, 5.8g of N-methylpyrrolidone, 0.76g of methacrylic anhydride, 2.1g of dimethylaminoethyl acrylate, and 4.2g of potassium humate for later use; B. stir and dissolve 2-acrylamide-2-methylpropane sulfonic acid, N-methylpyrrolidone, methacrylic anhydride, dimethylaminoethyl acrylate, and potassium humate in water to obtain a mixed solution; C. adjust the pH of the mixed solution to 4.0 with sodium hydroxide; heat to 58.9°C, introduce nitrogen for 20 minutes, add initiator ammonium persulfate to initiate, and react for 5 hours to obtain a fluid loss reducer;
[0113] (3) adding the solid mixture into the slurry preparation water within 15 seconds at a stirring speed of 4000±200 rpm, and stirring for 35 seconds at a stirring speed of 12000±500 rpm to obtain a cement slurry system.
[0114] Example 3
[0115] Cement slurry test temperature: 180℃ Cement slurry density: 2.3g / cm 3
[0116] (1) 600 g of G-grade cement and 240 g of high-temperature anti-fading agent are mixed to obtain a solid mixture.
[0117] (2) Weigh 103 g of water, 3 g of fluid loss reducer, 12 g of retarder C-R41L, and 3 g of C-DF60L, and mix to obtain slurry water;
[0118] The high temperature anti-fading agent is a compound of spherical silicon dioxide with a crystalline structure and micro-silicon with an amorphous structure in a mass ratio of 7:1. The sphericity of the spherical silicon dioxide is greater than 96%, and the particle size is between 4-10μM. The micro-silicon is a gray powder with an average particle size of 0.1-1μM.
[0119] The specific preparation method of the fluid loss reducer is as follows: a. Weigh 62.7 g of 2-acrylamide-2-methylpropane sulfonic acid, 7.1 g of N-methylpyrrolidone, 1 g of methacrylic anhydride, 3 g of dimethylaminoethyl acrylate and 5.5 g of potassium humate in weight and set aside; b. Stir and dissolve 2-acrylamide-2-methylpropane sulfonic acid, N-methylpyrrolidone, methacrylic anhydride, dimethylaminoethyl acrylate and potassium humate in water to obtain a mixed solution; c. Use sodium hydroxide to adjust the pH of the mixed solution to 4.4; heat to 59.7° C., introduce nitrogen for 15 minutes, initiate with an initiator, and react for 5 hours to obtain a fluid loss reducer;
[0120] (3) adding the solid mixture into the slurry preparation water within 15 seconds at a stirring speed of 4000±200 rpm, and stirring for 35 seconds at a stirring speed of 12000±500 rpm to obtain a cement slurry system.
[0121] Example 4
[0122] Cement slurry test temperature: 180℃ Cement slurry density: 2.4g / cm 3
[0123] (1) 600 g of G-grade cement and 240 g of high-temperature anti-fading agent are mixed to obtain a solid mixture.
[0124] (2) Weigh 74 g of water, 3 g of fluid loss reducer, 12 g of retarder C-R41L, and 3 g of C-DF60L, and mix to obtain slurry water;
[0125] The high temperature anti-fading agent is a compound of spherical silicon dioxide with a crystalline structure and micro silicon with an amorphous structure in a mass ratio of 7:1. The sphericity of the spherical silicon dioxide is greater than 96%, and the particle size is between 4-10 μM. The micro silicon is a gray powder with an average particle size of 0.1-1 μM.
[0126] The specific preparation method of the fluid loss reducer is as follows: a. weigh 60.2g of 2-acrylamide-2-methylpropane sulfonic acid, 6.83g of N-methylpyrrolidone, 0.95g of methacrylic anhydride, 2.88g of dimethylaminoethyl acrylate and 5.34g of potassium humate in weight and set aside; b. stir and dissolve 2-acrylamide-2-methylpropane sulfonic acid, N-methylpyrrolidone, methacrylic anhydride, dimethylaminoethyl acrylate and potassium humate in water to obtain a mixed solution; c. adjust the pH of the mixed solution to 3.7 with sodium hydroxide; heat to 61.1° C., introduce nitrogen for 30 minutes, initiate with an initiator, and react for 6 hours to obtain a fluid loss reducer.
[0127] (3) adding the solid mixture into the slurry preparation water within 15 seconds at a stirring speed of 4000±200 rpm, and stirring for 35 seconds at a stirring speed of 12000±500 rpm to obtain a cement slurry system.
[0128] Example 5
[0129] Cement slurry test temperature: 210℃ Cement slurry density: 2.3g / cm 3
[0130] (1) 600 g of G-grade cement and 300 g of high-temperature anti-fading agent are mixed to obtain a solid mixture.
[0131] (2) Weigh 70 g of water, 42 g of fluid loss reducer, 15 g of retarder C-R41L, and 3 g of C-DF60L, and mix to obtain slurry water;
[0132] The high temperature anti-fading agent is a compound of spherical silicon dioxide with a crystalline structure and micro silicon with an amorphous structure in a mass ratio of 7:1. The sphericity of the spherical silicon dioxide is greater than 96%, and the particle size is between 4-10 μM. The micro silicon is a gray powder with an average particle size of 0.1-1 μM.
[0133] The specific preparation method of the fluid loss reducer is as follows: a. weigh 65g of 2-acrylamide-2-methylpropane sulfonic acid, 7.48g of N-methylpyrrolidone, 1.04g of methacrylic anhydride, 2.88g of dimethylaminoethyl acrylate and 5.34g of sodium humate by weight and set aside; b. stir and dissolve 2-acrylamide-2-methylpropane sulfonic acid, N-methylpyrrolidone, methacrylic anhydride, dimethylaminoethyl acrylate and sodium humate in water to obtain a mixed solution; c. adjust the pH of the mixed solution to 3.2 with sodium hydroxide; heat to 63.1° C., introduce nitrogen for 30 minutes, initiate with an initiator, and react for 4 hours to obtain a fluid loss reducer.
[0134] (3) adding the solid mixture into the slurry preparation water within 15 seconds at a stirring speed of 4000±200 rpm, and stirring for 35 seconds at a stirring speed of 12000±500 rpm to obtain a cement slurry system.
[0135] Example 6
[0136] Cement slurry test temperature: 210℃ Cement slurry density: 2.4g / cm 3
[0137] (1) 600 g of G-grade cement and 300 g of high-temperature anti-fading agent are mixed to obtain a solid mixture.
[0138] (2) Weigh 67 g of water, 42 g of fluid loss reducer, 15 g of retarder C-R41L, and 3 g of C-DF60L, and mix to obtain slurry water;
[0139] The high temperature anti-fading agent is a compound of spherical silicon dioxide with a crystalline structure and micro silicon with an amorphous structure in a mass ratio of 7:1. The sphericity of the spherical silicon dioxide is greater than 96%, and the particle size is between 4-10 μM. The micro silicon is a gray powder with an average particle size of 0.1-1 μM.
[0140] The specific preparation method of the fluid loss reducer is as follows: a. weighing 65g of 2-acrylamide-2-methylpropane sulfonic acid, 7.48g of N-methylpyrrolidone, 1.04g of methacrylic anhydride, 2.88g of dimethylaminoethyl acrylate and 5.34g of sodium humate in weight and setting aside; b. stirring and dissolving 2-acrylamide-2-methylpropane sulfonic acid, N-methylpyrrolidone, methacrylic anhydride, dimethylaminoethyl acrylate and sodium humate in water to obtain a mixed solution; c. adjusting the pH of the mixed solution to 4.6 with sodium hydroxide; heating to 59.5° C., introducing nitrogen for 20 minutes, initiating with an initiator, and reacting for 5 hours to obtain a fluid loss reducer.
[0141] (3) adding the solid mixture into the slurry preparation water within 15 seconds at a stirring speed of 4000±200 rpm, and stirring for 35 seconds at a stirring speed of 12000±500 rpm to obtain a cement slurry system.
[0142] Comparative Example 1
[0143] Cement slurry test temperature: 180℃ Cement slurry density: 2.3g / cm 3
[0144] (1) 600 g of G-grade cement and 300 g of high-temperature anti-fading agent are mixed to obtain a solid mixture.
[0145] (2) Weigh 103 g of water, 36 g of fluid loss reducer, 12 g of retarder C-R41L, and 3 g of C-DF60L, and mix to obtain slurry water;
[0146] Wherein, the high temperature decay agent is 300 mesh silicon powder, and the mass percentage of silicon dioxide is greater than 97%;
[0147] The specific preparation method of the fluid loss agent is:
[0148] a. Weigh 62.7 g of 2-acrylamide-2-methylpropane sulfonic acid, 7.1 g of N-methylpyrrolidone, 1 g of methacrylic anhydride, 3 g of dimethylaminoethyl acrylate and 5.5 g of sodium humate in portions for later use; b. Stir and dissolve 2-acrylamide-2-methylpropane sulfonic acid, N-methylpyrrolidone, methacrylic anhydride, dimethylaminoethyl acrylate and humate in water to obtain a mixed solution; adjust the pH of the mixed solution to 4.4 with sodium hydroxide; heat to 59.7° C., introduce nitrogen for 15 min, initiate with an initiator, and react for 5 h to obtain a fluid loss reducer;
[0149] (3) adding the solid mixture into the slurry preparation water within 15 seconds at a stirring speed of 4000±200 rpm, and stirring for 35 seconds at a stirring speed of 12000±500 rpm to obtain a cement slurry system.
[0150] Comparative Example 2
[0151] Cement slurry test temperature: 210℃ Cement slurry density: 2.3g / cm 3
[0152] (1) 600 g of G-grade cement and 300 g of high-temperature anti-fading agent are mixed to obtain a solid mixture.
[0153] (2) Weigh 70 g of water, 42 g of fluid loss reducer, 15 g of retarder C-R41L, and 3 g of C-DF60L, and mix to obtain slurry water;
[0154] The high temperature anti-fading agent is a compound of spherical silicon dioxide with a crystalline structure and micro silicon with an amorphous structure in a mass ratio of 7:1; the sphericity of the spherical silicon dioxide is greater than 96%, and the particle size distribution is between 4-10μM. The micro silicon is a gray powder with an average particle size of 0.1-1μM;
[0155] The fluid loss reducer is the polymer fluid loss reducer C-FL80L currently used by CNOOC Oilfield Services.
[0156] (3) adding the solid mixture into the slurry preparation water within 15 seconds at a stirring speed of 4000±200 rpm, and stirring for 35 seconds at a stirring speed of 12000±500 rpm to obtain a cement slurry system.
[0157] Comparative Example 3
[0158] Cement slurry test temperature: 210℃ Cement slurry density: 2.3g / cm 3
[0159] (1) 600 g of G-grade cement and 300 g of high-temperature anti-fading agent are mixed to obtain a solid mixture.
[0160] (2) Weigh 70 g of water, 42 g of fluid loss reducer, 15 g of retarder, and 3 g of C-DF60L, and mix to obtain slurry water;
[0161] The high temperature anti-fading agent is a compound of spherical silicon dioxide with a crystalline structure and micro-silicon with an amorphous structure in a mass ratio of 7:1. The sphericity of the spherical silicon dioxide is greater than 96%, and the particle size is between 4-10μM. The micro-silicon is a gray powder with an average particle size of 0.1-1μM.
[0162] The specific preparation method of the fluid loss agent is:
[0163] a. Weigh 68g of 2-acrylamide-2-methylpropanesulfonic acid, 10g of N,N-dimethylacrylamide, 8g of fumaric acid, 3g of sodium styrene sulfonate and 8g of long side chain monomers and set aside; b. Stir and dissolve 2-acrylamide-2-methylpropanesulfonic acid, N,N-dimethylacrylamide, fumaric acid, sodium styrene sulfonate and long side chain monomers in water to obtain a mixed solution; c. Use sodium hydroxide to adjust the pH of the mixed solution to 6.4; heat to 62.4°C, introduce nitrogen for 20 minutes, initiate with an initiator, and react for 6 hours to obtain a fluid loss reducer;
[0164] The retarder is the polymer retarder C-R40L currently used by CNOOC Oilfield Services.
[0165] (3) adding the solid mixture into the slurry preparation water within 15 seconds at a stirring speed of 4000±200 rpm, and stirring for 35 seconds at a stirring speed of 12000±500 rpm to obtain a cement slurry system.
[0166] Comparative Example 4
[0167] Cement slurry test temperature: 210℃ Cement slurry density: 2.4g / cm 3
[0168] (1) 600 g of G-grade cement, 900 g of a weighting agent (1200 mesh iron ore powder), and 300 g of a high-temperature anti-fading agent are mixed to obtain a solid mixture, wherein the high-temperature fading agent is 300 mesh silicon powder, wherein the mass percentage of silicon dioxide is greater than 97%.
[0169] (2) Weigh 396 g of water, 42 g of fluid loss reducer (C-FL80L), 15 g of retarder (C-R40L), and 3 g of C-DF60L, and mix to obtain slurry water.
[0170] (3) adding the solid mixture into the slurry preparation water within 15 seconds at a stirring speed of 4000±200 rpm, and stirring for 35 seconds at a stirring speed of 12000±500 rpm to obtain a cement slurry system.
[0171] Cement slurry performance test:
[0172] The cement slurry performance test was carried out in accordance with GB / T 19139 2012 "Test Methods for Oil Well Cement". The stability test was carried out in accordance with Chapter 15 of GB / T 19139 2012, the water loss test was carried out in accordance with Chapter 10 of GB / T19139 2012, the compressive strength test was carried out in accordance with Chapter 7 of GB / T 19139 2012, the thickening time test was carried out in accordance with Chapter 9 of GB / T 19139 2012, and the rheological properties test was carried out in accordance with Chapter 12 of GB / T19139 2012. The comprehensive properties of the cement slurries of Examples 1-6 and Comparative Examples 1-4 are summarized in Table 1, and the thickening time curves of the cement slurry systems of Examples 1-7 at high temperatures are shown in Table 1. Figure 1-Figure 6 .
[0173] Table 1 Summary of comprehensive properties of cement slurry
[0174]
[0175] Note: The symbol “-” in Table 1 means not applicable. The cement slurry has poor mixing ability and poor slurry fluidity, which will interfere with other performance tests of the cement slurry.
[0176] It can be seen from the above table that the cement slurry prepared in different embodiments has good mixing capacity, slurry fluidity, free liquid, water loss, cement stone stability and compressive strength, which all meet the requirements of cementing construction. The thickening curve is stable, and no abnormal gelling phenomenon such as core encapsulation and bulging occurs. Moreover, no weighting agent is added in the system, and the proportion of cement components in the solid phase is relatively high, so the 24h compressive strength of the cement stone is relatively high. The system formula is simple, and only four admixtures are used to complete the construction of the high-temperature and high-density cement slurry system. In Comparative Example 1, the high-temperature anti-decay agent used is 300-mesh silicon powder, which is more than the composite of spherical silicon dioxide and amorphous microsilicon used in the embodiment. The high-temperature anti-fading agent prepared does not have a high sphericity, so it is difficult to prepare the cement slurry, and the prepared cement slurry has poor fluidity; the fluid loss reducer in Comparative Example 2 is the polymer fluid loss reducer C-FL80L used by CNOOC Oilfield Services, which has a larger viscosity and poorer fluidity than the low-viscosity fluid loss reducer used in the example, so it is difficult to prepare the cement slurry, and the prepared cement slurry has poor fluidity; the retarder in Comparative Example 3 is the polymer retarder C-R40L used by CNOOC Oilfield Services, which does not have a dispersing effect compared to the dispersing retarder C-R41L used in the example, so the prepared cement slurry has poor fluidity. Comparative Example 4 is a high-density cement slurry system currently used by CNOOC Oilfield Services, which consists of cement, silica fume, weighting agent, fluid loss reducer, retarder, dispersant, and defoamer. The formula is relatively complex, and the ash laying time is longer than that of the high-density cement slurry system without weighting agent. After high-temperature curing, a large amount of weighting agent particles in the cement slurry settle significantly, there is a lot of free liquid, and the density difference between the upper and lower cement stones is also large. In addition, the high-temperature anti-decay agent uses 300-mesh silica fume, which is crystalline silicon. Compared with the effect of the compound of crystalline silicon and amorphous silicon in the embodiment, the high-temperature anti-decay effect is poor, so the 24h cement stone compressive strength is low.
[0177] The present invention has been disclosed above with preferred embodiments, but those skilled in the art should understand that these embodiments are only used to describe the present invention and should not be understood as limiting the scope of the present invention. It should be noted that all changes and substitutions equivalent to these embodiments should be deemed to be included in the scope of the claims of the present invention. Therefore, the scope of protection of the present invention should be based on the scope defined in the claims.
Claims
1. A cement slurry system, characterized in that: include: Cement, high temperature anti-decay agent, fluid loss reducer, retarder, defoaming agent.
2. The cement slurry system according to claim 1, characterized in that: Calculated by weight, it includes 100 parts by weight of cement, 30-70 parts by weight of high-temperature anti-fading agent, 1-8 parts by weight of fluid loss reducer, 0.5-4 parts by weight of retarder, and 0.1-1 parts by weight of defoamer.
3. The cement slurry system according to claim 1, characterized in that: Calculated by weight, it includes 100 parts by weight of cement, 35-50 parts by weight of high-temperature anti-fading agent, 2-7 parts by weight of fluid loss reducer, 1-3 parts by weight of retarder, and 0.5-1 part by weight of defoamer.
4. The cement slurry system according to any one of claims 1 to 3, characterized in that: The cement is Grade G oil well cement that meets API specifications.
5. The cement slurry system according to any one of claims 1 to 3, characterized in that: The high temperature anti-fading agent is composed of spherical silicon dioxide with a crystal structure and micro silicon with an amorphous structure in a mass ratio of (6-8):
1.
6. The cement slurry system according to claim 5, characterized in that: The sphericity of the spherical silicon dioxide is greater than 96%, and the particle size is 4-10 μM; the average particle size of the micro-silicon is 0.1-1 μM.
7. The cement slurry system according to any one of claims 1 to 3, characterized in that: The fluid loss additive is a graft copolymer of fulvic acid salt.
8. The cement slurry system according to claim 7, characterized in that: The fluid loss reducer is a copolymer of fulvic acid salt grafted with 2-acrylamide-2-methylpropanesulfonic acid, N-methylpyrrolidone, methacrylic anhydride and dimethylaminoethyl acrylate.
9. The cement slurry system according to claim 8, characterized in that: The fulvic acid salt is sodium fulvic acid or potassium fulvic acid.
10. The cement slurry system according to claim 8, characterized in that: The weight ratio of humate to 2-acrylamide-2-methylpropanesulfonic acid, N-methylpyrrolidone, methacrylic anhydride and dimethylaminoethyl acrylate in the fluid loss reducer is (4-7): (55-77): (6-13): (0.5-3): (2-6).
11. The cement slurry system according to any one of claims 1 to 3, characterized in that: The retarder is obtained by compounding lignin sulfonate and AMPS copolymer.
12. The cement slurry system according to claim 11, characterized in that: The lignin sulfonate is sodium lignin sulfonate or calcium lignin sulfonate.
13. The cement slurry system according to claim 11, characterized in that: The weight ratio of the lignin sulfonate to the AMPS copolymer is (0.5:4.5)-(1:4).
14. The cement slurry system according to any one of claims 1 to 3, characterized in that: The defoaming agent is an ester defoaming agent, an organosilicon defoaming agent or a silicone ether oil defoaming agent.
15. A method for preparing a cement slurry system, characterized in that: include: (1) weighing cement and high-temperature anti-fading agent according to a proportion, mixing and stirring to obtain a solid mixture; (2) weighing water, fluid loss reducer, retarder, and defoamer according to the proportion, mixing, and obtaining slurry water; (3) adding the solid mixture into the slurry preparation water within 15 seconds at a first stirring speed, and mixing at a second stirring speed to obtain a cement slurry system.
16. The method for preparing a cement slurry system according to claim 15, characterized in that: The first stirring speed is 4000±200 rpm; the second stirring speed is 12000±500 rpm.
17. The method for preparing a cement slurry system according to claim 15, characterized in that: The fluid loss additive is prepared by the following method: (1) stirring and dissolving 2-acrylamide-2-methylpropanesulfonic acid, N-methylpyrrolidone, methacrylic anhydride, dimethylaminoethyl acrylate, and fulvic acid salt in water according to a proportion to obtain a mixed solution; (2) adding alkali to adjust the pH of the mixed solution to 3-5, heating to 58-62° C., introducing nitrogen for 10-30 minutes, initiating the reaction with an initiator, and reacting for 4-6 hours to obtain a fluid loss reducer.
18. The method for preparing a cement slurry system according to claim 17, characterized in that: The alkali is sodium hydroxide; the initiator is sodium sulfate, potassium persulfate, ammonium persulfate or azobisisobutyramidine hydrochloride.
Citation Information
Patent Citations
Low-friction and high-density cement paste and preparation method thereof
CN113800832A
A high-density, anti-channeling, tough cement slurry system for shale gas cementing, its preparation method, and its application.
CN114426415B
Nano high-density anti-channeling cement paste and preparation method thereof
CN116332571A